Civil War and Poverty The Role of Poverty in Tajik Civil War - Sambulshoevna, Saltanatova Mizhgona (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This thesis deals with the civil war correlating poverty with the focus on the civil conflict of Tajikstan 1992- 1997. Responding to civil wars is difficult because the root causes of the conflicts are complex. Many states of Middle East, Asia and Africa experienced civil conflict, which erupted with sharp economic decline. The question raised here then is, why poor nations have the more probability of civil war rather than rich countries - academic researches on the causes of conflict demonstrate compellingly that poor countries are at an increase risk of civil conflict. The argument of the research is that, poverty alone is not the cause of civil war, its state institutions that cause poverty and increase the risk of civil war. This thesis focuses on interrelation of civil war and poverty. And answers the question, whether poverty is the principal reason for why poor countries are more civil war prone. The central question of the research is why there is a linkage between civil war and poverty?. Analyzing the situation, this research employs the model of intra war correlate poverty used by World Bank “Breaking the Conflict Trap ” to explore the motives that effect civil war, in particular economic factor that mostly impact poor counties by slowing the countries developing process. And it comes that, the low income areas suffer from it more because they are more vulnerable to civil war. The central point is that, it‟s not only poverty that causes civil conflict but civil conflict also effects poverty, by poverty it means, the economic factors that served to make the poor nation poorer . All this can be more clearly seen in the experience of the low income countries. Keywords: Civil war, Poverty, Tajik civil war.

ÖZ : Bu tez iç-savaşı ele alarak yoksulluğu ilişkilendirip Tacikistan‟da 1992‟den 1997‟e kadar olan savaşa odaklanmıştır. İç savaşlara yanıt vermek çok zordur çünkü kök nedenleri çok karışıktır. Orta Doğu‟daki çoğu devletler, özellikle Asya ve Afrika, iç savaş yaşayarak ciddi ekonomik düşüşlere sebep olmuştur. Burada sorulması gereken soru o zaman şudur: neden yoksul ülkelerin iç-savaş yaşama ihtimali zengin ülkelere göre yüksektir? Akademik araştırmaya göre yoksul (fakir) ülkelerin çatışmaya daha meyilli olduğu ve bu durumun artışının söz konusu olması mühtemeldir. Fakat asıl argüman, yoksulluk direk bire bir iç-savaşı tetiklemiyor, devlet kurumlarının yoksulluğa ve dolayısıyla iç-savaş riskini arttırıyor. Bu tez iç-savaş ile yoksulluk arasındaki karşılıklı ilişkiye bakmaktadır ve bu anlamda yoksulluğun iç-savaş için fakir ülkelerin ana nedeni olup olmadığına cevap verir. Araştırmanın ana sorusu şudur: iç-savaş ile yoksulluk arasında direk bir bağlantı var mıdır? Durumu analiz ederek, araştırma iç-savaş ile yoksulluğu ele alarak, Dünya Bankası “Çatışma Önleme Tuzağı” hakkındaki iç-savaşı etkileyen motiflere bakıp, yoksul ülkelerin belirli ekonomik faktörler ile onların kalkınma aşamalarına göz atacaktır. Sonuç itibari ile, az-gelirli olan bölgeler en çok darbeyi alan ve en hassas olan bölgelerden ibaret olması kaçınılmaz olmuştur. Tezde ana fikirlerden bir tanesi de aslında yoksulluğun iç-savaşı etkilemesi değil, diğer yandan, iç-savaşın yoksulluğa neden ve sebep olmasıdır ve yoksulluk denilirken, ekonomik faktörlerin yoksul bir ülkeyi nasıl fakirleştirdiğidir. Bunların hepsi daha net bir şekilde düşük-gelirli ülkelerin deneyimlerinde yaşamlarında görülmektedir. Anahtar Kelimeler: İç-savaş, yoksulluk, sefalet, Tacikistan iç-savaşı.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2016. Supervisor: Assoc. Prof. Dr. Erol Kaymak.
Keywords: Political Science and International Relations; Politics - Civil War - Tajikistan; Tajikistan - Politics and government; Civil war; Poverty; Tajik civil war